Retinoic acids and nuclear receptor signaling in liver development: Pathogenic roles in liver diseases - Wen Jia; Yang Bi (Pediatric Discovery)
Abstract Retinoic acid (RA) serves as a metabolic intermediate of vitamin A. It plays a crucial physiological role in regulating cell proliferation, differentiation, apoptosis, embryonic development, and immunomodulation. Once vitamin A enters the body in the form of retinol, it undergoes conversion into RA through the intestinal epithelium and liver. Subsequently, it interacts with retinoic acid receptors and retinoid X receptors within the cell nucleus, thereby regulating gene expression. Throughout liver development, RA exerts precise temporal control, stimulating liver growth, inducing RALDH2 expression in liver somatic epithelial cells, and influencing hepatocyte differentiation. Recent studies have consistently demonstrated the indispensable connection between RA deficiency and the development of liver diseases, including nonalcoholic fatty liver disease, chronic hepatitis, liver fibrosis, and liver tumors. Studying the mechanisms underlying the relationship between RA and disease can enhance our understanding and improve disease treatment. This paper provides a comprehensive review of the role of RA signaling in liver development and liver diseases.